SENAM KEGEL PENGARUHNYA TERHADAP PENYEMBUHAN LUKA PERENIUM PADA IBU NIFAS - Astri Yunifitri; Devy Lestari Nurul Aulia (Universitas Batam, 2022)
Perineal lacerations occur due to prolonged tissue damage that occurs during delivery, either due to pressure on the fetal head or shoulders or an episiotomy. Prolonged healing of perineal wounds can be caused by a lack of mobilization and exercise (Puerperal Gymnastics/Kegels). The purpose of this literature review is to explore the effect of puerperal exercise on peresnium wound healing. The research method is a qualitative analysis approach with a literature study or literature research method. From the search results, it is found that there is a significant relationship between Kegel exercises and perineal wound healing. The results of this literature review are expected to be applied by health workers to postpartum mothers to accelerate the healing of perineal wounds.